Critical Social Psychology / An Introduction - Gough Brendan; Mcfadden Majella (Palgrave Macmillan, 2001)
This book introduces students to key themes and debates arising from this burgeoning - and often complex - field. Preface, Acknowledgements, Critical Social Psychology: An Introduction, A Critical Look at Cognitive-Experimental Social Psychology, Doing Critical Social Psychology, Deconstructing the Self, Social Influence, Re-Viewing Sex Difference, Sexualities and Psychology, Aggression in Social Contexts, Prejudice in Practice, Reflections on Critical Social Psychology, Postscript, Glossary, References, Index.